CAPILLARY HAEMANGIOMA OF LOWER LIP IN AN AFRICAN PATIENT - Bajpai, Manas; Pardhe, Nilesh; Kumar, Manish (Journal of Ayub Medical College Abbottabad, 2017)
Haemangioma is one of the commonest benign vascular tumours affecting 10-12% of infancy. Approximately 50% of haemangiomas resolve by the age of 5 years and 90% resolve by 9 years of age. Rarely haemangiomas persist and required treatment.1 A 26-year-old African male presented with a painful swelling of lower lip for 1 year. The swelling was initially small and gradually reached the present size. Past medical history and family history of the patient was non - contributory to the presenting symptom. Clinical examination of the patient revealed a radish to purplish, fluctuant swelling of the lower lip involving the whole lower lip measuring about 3Ã—2 cm. (Figure-1) On palpation it was soft to firm no signs of discharge and ulceration were found. Blenching was found to be positive on diascopy. Fine Needle aspiration cytology was performed which was performed and repeated aspirations yielded fresh blood. The microscopical examination of the aspirate revealed collection of numerous RBCs. (Figure-2) 5% ethamolin 2 ml was injected in the lesion and Incisional biopsy was taken under local anaesthesia. The specimen was submitted to the Department of Oral and Maxillofacial Pathology for microscopic evaluation. The microscopic examination of soft tissue section revealed a highly vascular connective tissue stroma comprised of numerous dilated blood vessels containing RBCS and lined by endothelial cells. (Figure 3 & 4) The stroma was sparse with minimal inflammatory component. An area of haemorrhage was noted with the collection of abundant hemosiderin pigmentation. The overlying epithelium was normal stratified squamous epithelium without dysplasia. Based on these features a final diagnosis of capillary haemangioma was given. Pigmented lesions are commonly found in the mouth. Such lesions represent a variety of clinical entities, ranging from physiologic changes to manifestation of systemic illness and malignant neoplasm.1 Haemangiomas are considered common in head and neck but rare in oral cavity and lips.2 The differential diagnoses of haemangioma include lymphangioma, Intra vascular papillary endothelial hyperplasia and pyogenic granuloma.3 A colour Doppler ultrasound is required to confirm the association of feeder vessel. Sclerosing agents may be used for diagnostic and therapeutic purposes. In the present case also ethamolin was used for incisional biopsy. Growing haemangiomas can be treated effectively by systemic drug therapy, sclerotherapy, laser therapy or combined therapy.